BENEFIT RECIPIENT PROBLEMATICS IN PMB-RW TRAINING ACTIVITIES IN UMBAN SARI KELURAHAN KECAMATAN RUMBAI PEKANBARU - Ria Rizkia Alvi; Dafetta Fitrilinda; Fajri Muharram; Anggoro Anggoro (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2020)
This study aims to determine the problems of beneficiaries in PMB-RW training activities in Kelurahan Umban Sari Kecamatan Rumbai Pekanbaru. This research is an evaluation research with a qualitative approach using the CIPP Model from Stufflebeam (1985) which consists of evaluation of context, input, process and product. The research will be conducted in Kelurahan Umban Sari Kecamatan Rumbai PekanbaruThe subjects of this study were the village head, PMB-RW Facilitators and the beneficiaries. The data was collected by using the interview method, documents, and observations. Furthermore, the data obtained were analyzed using interactive model data analysis (Miles & Huberman, 2007), namely data reduction, data presentation, and conclusion drawing. In order to obtain the validity of the data, triangulation was carried out, discussions with experts, and observation extension. The results showed that the problems of beneficiaries in PMB-RW training activities in Kelurahan Umban Sari Kecamatan Rumbai Pekanbaru were no post-training mentoring and coaching, no venture capital and did not dare to take risks (fear of failure), no motivation from beneficiaries. These problems make PMB-RW training not have an impact on economic, social welfare and expansion of job opportunities even though community knowledge has been obtained in PMB-RW training. This ability cannot be used as a job because there is no capital for equipment and so on in creating fields and expanding job opportunities for the community so that the big goals of the PMB-RW program have not been achieved.